Primary Ciliary Dyskinesia - An Update on the Genetics of Underlying Pathological Mechanisms - Karikalan, Barani; Chakravarthi, Srikumar (Current Respiratory Medicine Reviews, 2023)
One of the rapidly growing groups of diseases known as ciliopathies is primary ciliary dyskinesia (PCD), a rare hereditary illness of the motile cilia. Different clinical symptoms of primary ciliary dyskinesia include infertility, left-right lateralization abnormalities, and chronic upper and lower respiratory tract disorders. Our knowledge of the genetics underlying primary ciliary dyskinesia has significantly increased in recent years. Involved in the formation, shape, and operation of motile cilia are axonemal, cytoplasmic, and regulatory proteins that are encoded by a rising number of disease-associated genes and pathogenic mutations. We now have a better grasp of the clinical signs and symptoms of motile ciliopathies because of advances in our understanding of cilia genetics and the function of the proteins expressed. These developments have altered how we approach primary ciliary dyskinesia diagnostic testing. The clinical characteristics of primary ciliary dyskinesia, the evolution of diagnostics, and the discovery of previously unknown genotype-phenotype connections in primary ciliary dyskinesia will all be covered in this review paper.
Keywords: genetics